Collecting as Man’s Intimate Relationship with Things: An Ethnographic Study of Collecting the Ordinary in South‑western France - Markovová, Dana (Lidé města, 2024)
This paper develops an anthropological approach in order to examine the collecting of “ordinary things” as a private, home-based, leisure activity. The research was conducted in the region of Nouvelle Aquitaine, located in the south-west of France, where the author has lived since 2012. The aim of this ethnographic research is to describe the interaction between two interconnected worlds, the human and the material. Objects, as such, cannot be attributed to any single category – be they utilitarian, decorative, or fetish-objects etc. In fact, every object has the capacity of becoming singular in the eyes of the possessor. Their varying importances will depends on the owner’s perspective and the meaning he or she may attribute to them. They become a part of peoples’ lives, shaping and helping to create their identity. Collectors, taken in by these objects, reserve for them a special place in their homes, going so far as devising special rules for their use.